A U.S. energy bill at last. - Sweet, W.
This paper reports on a US Congress-approved comprehensive energy law to make electric power reliability rules mandatory so that the kinds of lapses on the part of utility managers that led to the big blackout of August 2003 will now be punishable. The energy bill also allocates billions of dollars for a variety of incentives to encourage energy efficiency and conservation as well as greater use of wind, solar, and nuclear energy.
Keywords: August 2003 blackout; US Congress; Comprehensive energy law; Electric power reliability rules; Energy bill; Energy conservation; Energy efficiency; Energy production improvement; Utility managers